Arts policy and practice for disabled children and young people: towards a 'practice spectrum' approach. Issue 3 (15th March 2016) - Newsinger, Jack; Green, William
Abstract: This article argues for an approach to the evaluation of arts policy and practice for disabled children and young people that goes beyond the dialogic antagonism between Disability Arts and community arts, and towards a 'practice spectrum'. Little is known about the extent to which a Disability Arts perspective has extended into arts policy and practice for disabled children and young people. The article aims to redress this knowledge gap. It is based upon two sets of data collected in relation to the East Midlands region of England during 2014. First, a critical evaluation was conducted of official and institutional attitudes to arts practice with disabled children and young people. Second, interviews exploring contemporary practice were conducted with 24 arts organisations. Their practice represents a diverse range of art forms and programmes undertaken in the region, and a range of attitudes and positions taken towards disabled children and young people. We argue that the best way to conceive of current practice is as a spectrum, as opposed to an antagonism between community arts and Disability Arts perspectives. There is, however, little evidence of the penetration of a Disability Arts perspective into policy and practice for children and young people.